Healthy Aging: A Key Strategy for Retaining Skilled Nursing Professionals - Nena, Evangelia; Truxillo, Donald M.; Kiran, Sibel; Pobric, Alma; Rusu, Horatiu; Sotiroska Ivanoska, Kalina; Tripkovic, Katica; Gligor, Laura Elena; Katsaouni, Maria (Scilight Press Pty Ltd, 2025)
Background: Early retirements and decreasing job retention rates have resulted in a growing shortage of nursing staff in the healthcare systems of many countries. Recently, the World Health Organization and the European Commission have joined forces to attract and retain nurses in their systems in a period of increasing demand for healthcare services, due to population aging. While recruiting and training new nurses is a necessary long-term solution, it is equally important for policymakers to focus on retaining the current workforce, as to ensure continuity of care. Aim: This paper aims to review current literature and to discuss the key aspects of this critical issue, focusing on the concept of healthy aging and its significance as a key strategy for retaining nursing staff. Design: This discursive paper explores published literature highlighting the interaction between aging and the challenges that nursing staff faces in daily practice. It also examines global trends in retirement patterns and proposes strategies to retain the aging workforce, with a particular focus on succession planning and knowledge transfer. Results-Conclusion: Both general and more targeted approaches that have been proposed are necessary to enhance nursing staff retention. These approaches include the concept of promoting healthy aging, which can play a key role in this regard. Implications: This paper addresses the nursing staff shortage, highlighting strategies that have been proposed as to prioritize staff retention for healthcare providers and personnel managers.